2011
DOI: 10.1063/1.3533642
|View full text |Cite
|
Sign up to set email alerts
|

Energy level alignment, electron injection, and charge recombination characteristics in CdS/CdSe cosensitized TiO2 photoelectrode

Abstract: The band-edge levels of CdS-, CdSe-, and CdS/CdSe-sensitized TiO2 electrodes were determined by ultraviolet photoelectron spectroscopy (UPS) to explore the reason leading to the high performance of the TiO2/CdS/CdSe electrode. The obtained UPS results show the stepwise energy level in the TiO2/CdS/CdSe electrode, indicating energy level alignment occurrence between CdS and CdSe in the TiO2/CdS/CdSe. Time-resolved photoluminescence and open-circuit photovoltage decay experiments reveal that the photogenerated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 21 publications
2
57
0
Order By: Relevance
“…For CdS/CdSe co-sensitized electrode such decay start after 550 nm for QRs 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 20 it is observed that the CdS/CdSe CB is -3.49 eV due to the Fermi-level alignment 39 showing the CB above of the TiO 2 CB obtaining a favorable electron injection and increase of V oc from 542 mV to 575 mV. …”
Section: Samplementioning
confidence: 92%
“…For CdS/CdSe co-sensitized electrode such decay start after 550 nm for QRs 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 20 it is observed that the CdS/CdSe CB is -3.49 eV due to the Fermi-level alignment 39 showing the CB above of the TiO 2 CB obtaining a favorable electron injection and increase of V oc from 542 mV to 575 mV. …”
Section: Samplementioning
confidence: 92%
“…Metal oxide semiconductors are generally stable in aqueous environments and are cheap which leads them to be widely promoted as among the most promising materials for solar-photon-driven water splitting. 1,6,7 Although a large number of semiconductor materials have been developed as good candidates for photoelectrodes in past decades, 8,9 the solar-hydrogen conversion efficiencies of these recognized materials are still not high enough due to low light absorption and high recombination of electron-hole pairs. 5,10 Therefore, the design of efficient solar-active nanostructured PEC cell has been the topic of considerable research.…”
mentioning
confidence: 99%
“…The OCVD technique was used to monitor the subsequent decay of photovoltage after turning off the illumination. Figure 7a shows the voltage decay curves of the DSSCs based on SNC and SNC_Z photoanodes and the calculated τ e using Equation (1) [33,34]:…”
Section: Resultsmentioning
confidence: 99%